Perencanaan E-Sport Center Dengan Penerapan Arsitektur Futuristik Di Denpasar – Bali - Ramadhani Estu Segara Aji; Ni Putu Ratih Pradnyaswari Anasta Putri; I Nyoman Gede Mahaputra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Currently Indonesia has been influenced by the existence of e-sports (electronic sports), this electronic sport conducts regional or national tournaments or competitions in online games. With the existence of e-sports, it is an opportunity for gamers / online game players in Indonesia to participate in the world of e-sports and play online games. Therefore it takes a place for gamers to gather and also as a place to hold matches. The process of making a forum or place that is centered on providing entertainment about game developments in Denpasar City with an innovative process of forming, iconic buildings and friendly to the urban environment. The design concept of the E-sport center has a futuristic architectural approach with a facade combined with wood that does not have ornaments and is plain, futuristic and minimalist so that it will become the center of development in playing games, because it does not only provide a gathering place, but also a Tournament Place to watch competitions. , Gaming Area, game shop, and also Cafe.